Association of Intrarenal B-Cell Infiltrates with Clinical Outcome in Lupus Nephritis: A Study of 192 Cases - Yan Shen; Chuan-Yin Sun; Feng-Xia Wu; Yi Chen; Min Dai; Yu-Cheng Yan; Cheng-De Yang (Clinical and Developmental Immunology)
Background. Lupus nephritis (LN) remains a major cause of morbidity and end-stage renal disease. Dysfunction of B lymphocytes is thought to be important in the pathogenesis of SLE/LN. Intrarenal B cells have been found in several forms of inflammatory kidney diseases although their role in LN renal is not well defined. Methods. Intrarenal B cells were analyzed in 192 renal biopsies from patients diagnosed with lupus nephritis. Immunohistochemical staining of serial sections was performed for each LN patient using CD20, CD3, and CD21 antibodies. Results. Intrarenal B cells were more likely to be associated with class IV LN and were mainly distributed in the renal interstitium, with very few in the glomerulus. The systemic lupus erythematosus disease activity index (SLEDAI), blood urea nitrogen, and serum creatinine levels were all significantly greater in the LN-B cell groups (all P<0.05). LN renal activity and chronicity indices correlated with B-cells infiltrates (all P<0.0001). Renal biopsies were classified into four distinct categories according to the organizational grade of inflammatory cell infiltrates. Germinal center- (GC-) like structures were not identified in any LN biopsies. Conclusion. It is hypothesized that intrarenal B cells enhance immunological responses and exaggerate the local immune response to persisting autoimmune damage in the tubulointerstitium.